Combating challenges in CAR-T cells with engineering immunology - Wang, Clement Yisai; Ting Cheung, Stephanie Po; Sugimura, Ryohichi (Frontiers in Cell and Developmental Biology, 2022)
Chimeric antigen receptors (CAR) T cells (CAR-T) mark a significant step towards producing safe and effective personal anticancer treatments. CAR-T strategies engineers the T cells from the patients to allow specific binding to a tumour-specific antigen. CAR-Ts are a second-wave offensive strategy to clear out remaining chemotherapy-resistant tumour cells. Though showing practical antitumor abilities in multiple haematological malignancies and solid tumour cancers, the issues of antigen escape, tumour infiltration/penetration, and toxicity side effects limit the usage of prolonged CAR-T therapies. However, engineering immunology has exploited human stem cell-based CAR-T therapies and the development of CAR-M (macrophage) therapies to combat the disadvantages of conventional CAR-T therapies. In this review, we will highlight the challenges of CAR-T therapies and combat them with engineering immunology for cancer immunotherapy.